Consumer Bankruptcy: A Fresh Start - Livshits, Igor; MacGee, James; Tertilt, Miche`le (American Economic Review, 2007)
There has been considerable public debate on the relative merits of alternative consumer bankruptcy rules. The option to discharge one’s debt provides partial insurance against bad luck, but by driving up interest rates makes lifecycle smoothing more difficult. We construct a quantitative model of consumer bankruptcy to address this trade-off. We argue that such a model should have three key feature: a life-cycle component, idiosyncratic earnings uncertainty and expense uncertainty (exogenous negative shocks to household balance sheets). We further show that transitory and persistent earnings shocks have very different implications for evaluating bankruptcy rules – while persistent shocks make bankruptcy option desirable, transitory shocks have the opposite implication. Our findings suggest that the current US bankruptcy system may be desirable for reasonable parameter values.